The problem of synthesis of functionally steady information systems in railway transport - Cherneva, Galina; Andonov, Antonio; Hubenová, Zoya (Univerzita Pardubice, 2010)
Control and operation exploitation of high-rate railway transport are the fundamental object of programs of European Council where the rail traffic information system is the real touchstone of European co-operation.In the article examined weigh complex of researches in area of the functional steady information systems. The paper presents the problem about the functional stability of radio communication systems of safety responsibility in railway transport and proposes a number of approaches to solve it. The following problems have been solved: 1. Setting the problem of the functional stability of radio communication systems of safety responsibility and giving reasons for an approach to its solution. 2. Examination on the possibilities of building functionally stable information systems. The decided tasks and got results are analyzed perspective directions of researches are described in this area stability.
Keywords: functional stability; information systems